Malawi population and housing census technological trajectory: Unpacking 2018 experience - Kanyuka, Mercy; Ndawala, Jameson; Chirwa, Isaac; Makwemba, Medson; Phiri, Richard A.P.; Singano, Chisomo; Kapaswiche, Grevazio (Statistical journal of the IAOS, 2020)
Globally, with increase in need for evidence for relevant and effective responses in this century, holistic stocktaking and documentation of subjects has been heightened. In the same vein, Malawi has successfully conducted censuses from 1966 to 2018. Unlike other censuses, the latest round adopted use of Satellite imagery for mapping, Computer Assisted Personal Interviewing (CAPI) technology for data capturing and wireless and on-line data transmission to significantly reduce processing time and improve reliability and timeliness of census results. However, in the face of CAPI and built-in data quality control features, data processing is irreplaceable and key since censuses are never perfect and errors do occur. Further, whilst incorporation of technology demonstrates benefits and merits, the approach comes with some logistical, financial and technical implications. It is also evident that Knowledge sharing between National Statistical Offices (NSOs) is worthwhile, and incorporation of technological innovations has advantages irrespective of significant costs. Finally, being optimistic, positive minded and pro-active is key to implementation of a successful census.